Clinical pediatric anesthesia : a case-based handbook - Goldschneider, Kenneth R. (Oxford University Press, 2012)
"Through 71 case presentations, Clinical Pediatric Anesthesia covers the field of pediatric anesthesiology with a practical, point-of-care approach. Each concisely written case is organized by introduction, learning objectives, case presentation, discussion, summary, annotated references, and further reading. In a style akin to the oral board examinations, discussions are framed as questions and answers to encourage thorough analysis and understanding by the reader. Key words are highlighted to emphasize important points, and annotated references allow for further exploration of topics. Multiple approaches often exist for the care of children in any given situation, so various options are discussed when appropriate with advantages and disadvantages closely examined. Since questions posed by real-life clinical situations call for active thinking, this case-based book promotes the same evaluation and decision-making skills required of the pediatric anesthesia clinician"--Provided by publisher